2012
DOI: 10.1016/j.devcel.2012.04.014
|View full text |Cite
|
Sign up to set email alerts
|

MT1-MMP Inactivates ADAM9 to Regulate FGFR2 Signaling and Calvarial Osteogenesis

Abstract: MMP14 encodes a membrane-tethered metalloproteinase MT1-MMP, capable of remodeling the extracellular matrix and modulating receptors on the cell surface. Loss of MT1-MMP results in craniofacial abnormalities. Here we show that MT1-MMP forms a complex with FGFR2 and ADAM9 in osteoblasts and proteolytically inactivates ADAM9, hence protecting FGFR2 from ADAM9-mediated ectodomain shedding on the cell surface. In Mmp14-/- osteoblasts, FGF-induced proliferation and downstream signaling are specifically compromised,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
82
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 50 publications
4
82
0
Order By: Relevance
“…MMP-14 degrades extracellular matrix components (i.e. fibrillar collagen and gelatin), activates enzymes such as MMP-2 and MMP-13, sheds cell surface proteins (Chan et al, 2012;Egeblad and Werb, 2002;Itoh and Seiki, 2006;Koshikawa et al, 2011;Koshikawa et al, 2010), and was recently shown to prevent collagen-induced apoptosis (Maquoi et al, 2012). The activity of MMP-14 is regulated by multiple mechanisms, including activation by cell surface proteins such as tetraspanin CD151 and aVb3 integrins (Deryugina et al, 2004;Gonzalo et al, 2010;Hadler-Olsen et al, 2011;Itoh and Seiki, 2004;Yañez-Mó et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…MMP-14 degrades extracellular matrix components (i.e. fibrillar collagen and gelatin), activates enzymes such as MMP-2 and MMP-13, sheds cell surface proteins (Chan et al, 2012;Egeblad and Werb, 2002;Itoh and Seiki, 2006;Koshikawa et al, 2011;Koshikawa et al, 2010), and was recently shown to prevent collagen-induced apoptosis (Maquoi et al, 2012). The activity of MMP-14 is regulated by multiple mechanisms, including activation by cell surface proteins such as tetraspanin CD151 and aVb3 integrins (Deryugina et al, 2004;Gonzalo et al, 2010;Hadler-Olsen et al, 2011;Itoh and Seiki, 2004;Yañez-Mó et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, cell invasion into dense matrices, such as basement membranes, requires ECM proteolysis and remodeling to clear space and create tracks along which cells can migrate more efficiently (Hotary et al, 2006;Sabeh et al, 2004;Sabeh et al, 2009). Cell-associated proteolytic activity is also likely to be important for cleavage of non-ECM targets, including latent growth factors and integrins (Black et al, 1997;Chan et al, 2012;Izumi et al, 1998;Kajita et al, 2001;Kessenbrock et al, 2010;Koshikawa et al, 2010;Lyons et al, 1990;Moss et al, 1997;Mu et al, 2002;Turk et al, 2001;Yu and Stamenkovic, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…1). 9 These data suggested that MT1-MMP is tightly connected with FGF signaling in calvarial development.…”
Section: Mt1-mmp As a Positive Modulator Of Fgf Signalingmentioning
confidence: 89%
“…1). 9 It is interesting that ADAM9-mediated cleavage of FGFR2 results in the formation of C-terminally truncated fragments with unclear functions. It is likely that the accumulation of truncated FGFR2 fragments inhibits FGF signaling in a dominant-negative manner, but further investigation will be required to confirm that.…”
Section: Mt1-mmp and Fgf Signaling In Intramembranous Ossificationmentioning
confidence: 99%